RISIKO KESEHATAN DALAM MEMPERTAHANKAN EKONOMI KELUARGA PADA PETANI PENYEMPROT PESTISIDA DI DESA LARANGAN KABUPATEN BREBES - Ilyas Ibrahim (FORUM ILMIAH KESEHATAN, 2022)
Intense use of toxic chemicals can have a bad effect on the environmental ecosystem and public health. Farmers as pesticide sprayers on agriculture have a risk of being exposed to pesticides. The problem of family economic needs makes farmers survive the health risks arising from these toxic materials. Long-term exposure to chemical pesticides can have a bad effect on human health, especially systemic diseases. Difficult economic pressures related to family income, family needs and family health cause farmers to surrender to health risks. This study aims to describe the health risks in maintaining the family economy of pesticide spraying farmers in Brebes Regency, Indonesia. This research used qualitative methods with case studies and interviews with informants (family heads). The respondents were interviewed to find out the health and economic conditions of their families. The data collected were then compiled to describe the health and economic conditions experienced by the head of the family. Respondents were interviewed that economic pressures were so difficult that they ignored the health risks they faced. Maintaining the family's economy in a difficult life, family heads are willing to face all kinds of illnesses they suffer. Pesticide spraying activities on agriculture are carried out routinely as farmer workers to meet the economic needs of the family. Pesticide poisoning that cause physical health disorders, the heat of the sun, rain and fatigue as health risks are ignored because there is no other choice to maintain the family economy. Keywords: health risks; economy; farmer; pesticides ABSTRAK Penggunaan bahan kimia beracun secara intensif dapat berdampak buruk pada ekosistem lingkungan dan kesehatan masyarakat. Petani sebagai penyemprot pestisida pada pertanian memiliki risiko terkena pestisida. Masalah kebutuhan ekonomi keluarga membuat petani bertahan dari risiko kesehatan yang ditimbulkan dari bahan beracun tersebut. Paparan pestisida kimia dalam jangka panjang dapat berdampak buruk bagi kesehatan manusia, terutama penyakit sistemik. Tekanan ekonomi yang sulit terkait pendapatan keluarga, kebutuhan keluarga dan kesehatan keluarga menyebabkan petani menyerah pada risiko kesehatan. Penelitian ini bertujuan untuk mendeskripsikan risiko kesehatan dalam mempertahankan ekonomi keluarga petani penyemprot pestisida di Kabupaten Brebes. Indonesia. Penelitian ini menggunakan metode kualitatif dengan studi kasus dan wawancara dengan informan (kepala keluarga). Responden diwawancarai untuk mengetahui kondisi kesehatan dan ekonomi keluarganya. Data yang terkumpul kemudian disusun untuk menggambarkan kondisi kesehatan dan ekonomi yang dialami oleh kepala keluarga. Temuan; responden diwawancarai bahwa tekanan ekonomi begitu sulit sehingga mereka mengabaikan risiko kesehatan yang mereka hadapi. Kesimpulannya aktivitas penyemprotan pestisida di pertanian dilakukan secara rutin sebagai pekerja petani untuk memenuhi kebutuhan ekonomi keluarga. Keracunan pestisida yang menimbulkan gangguan kesehatan tubuh, panasnya matahari, kehujanan dan kelelahan merupakan risiko kesehatan yang diabaikan, karena tidak ada pilihan lain untuk mempertahankan ekonomi keluarga.Kata kunci: risiko; kesehatan; ekonomi; petani; pestisida